The weaving explorer : ingenious techniques, accessible tools & c reative projects with yarn, paper, wire & more - Jarchow, Deborah; Steege, Gwen, 1940- (North Adams, MA : Storey Publishing, 2019)
"The Weaving Explorer takes inspiration from the world of folk weavi ng traditions, adding a contemporary spin by introducing an unexpected range of materials and home dec projects"--
Weaving in circles -- Pin-loom weaving -- Framed! -- Tapping into ta pestry -- Backstrap weaving -- Frameless weaving -- Free and easy -- Ro ck, paper, ribbon!
Includes index.
Keywords: Hand weaving; Hand weaving -- Patterns